Relationship between filial responsibility, self-esteem, emotional regulation and subjective well-being among Pakistani community-dwelling older adults - Hassan, Sumara Masood Ul (2019)
Prior research on the psychosocial factors of subjective well-being as one of the key indicators of ageing well was mainly conducted in Western cultures and with little emphasis on mechanisms underlying older adults’ subjective well-being. This correlational study aimed to determine the association of adult attachment, relationship quality, religiosity, filial responsibility, self-esteem, and emotional regulation with subjective well-being; the direct effects of filial responsibility, self- esteem, and emotional regulation on subjective well-being after controlling for the influences of covariates; and the mediating effects of self-esteem and emotional regulation on the relationship between filial responsibility and subjective well-being. Multistage cluster random sampling method was utilised to collect data from 400 older adults from Rawalpindi, Pakistan. The Concise Measure of Subjective Wellbeing (COMOSWB), The Experiences in Close Relationships-Revised Scale (ECR-RS), Affective Scale, Revised Intrinsic/Extrinsic Religious Orientation Scale (I/E-R), filial expectation and filial behaviour scales, Rosenberg Self-Esteem Scale (RSES) and The Emotional Regulation Questionnaire (ERQ) were administrated to the respondents through the interview method. The results showed that adult attachment, relationship quality, religiosity, filial behaviour, self-esteem, and emotional regulation were significantly while filial expectation was not significantly associated with subjective well-being. Filial behaviour of respect, self-esteem and emotional regulation were major predictors of subjective well-being after controlling for the influences of covariates. These variables explained 72% of the variability in subjective well-being. Structural equation modeling demonstrated that self-esteem and cognitive reappraisal of emotional regulation partially mediated the relationship between filial behaviour of respect but failed to function as significant mediators on the association of filial expectation and filial behaviour of daily maintenance with subjective well-being. Besides, suppression of emotional regulation did not show a mediating effect on the relationship between filial responsibility and subjective well-being. Overall, this study provides valuable insights regarding the importance of eldest sons’ filial behaviour of respect in their older parent’s lives and highlights the roles of self-esteem and emotional regulation in the relationship between filial responsibility and older adults ‘subjective well-being.